Diferentes vínculos profissionais dos professores com a instituição de ensino superior e sua influência sobre o sentido do trabalho - Barbosa, Elaine Sampaio Teles (2017)
The research question that guided this study was: what is the meaning of the work for teachers of a Higher Education Institution (HEI) that work under different working relationships? In order to answer this question, we conducted an empirical research of ethnographic character, in which we interviewed 45 teachers from a HEI, comparing different types of links in the Institution. Interviews when authorized were recorded and transcribed and submitted to discourse analysis. In the analysis, we use categories defined a priori about Morin's sense of work, as well as the categories that emerged spontaneously from the interviewees' statements and finally we diagnosed the existence of an axial category. This study identified that teacher’s work fits in all characteristics of Morin's work, highlighting respectively: work as being morally acceptable, work as source of satisfactory human relations and work intrinsically satisfactory. The result also identified that employment relationship makes no difference in the sense of work for a teacher, but how long they’ve been teaching in the Institution and the age of the interviewees. The field has revealed that the sense of belonging is not perceived by guest teachers or by employed teachers who are early in their careers, differently from older teachers with more time at Institution. For younger guest teachers, being linked to the institution's brand is enough to achieve job satisfaction; on the other hand, for older guest teachers with more time at the HEI a relation of gratitude with the Institution was found. The classroom for employed teachers is understood as secondary since these professionals are evaluated by their researches and for the guest teacher there is an evaluation made by the students that is key to keep them in the Institution. There is no formal evaluation by the Institution on the performance of the teacher in the classroom in the different bonds. Thus, the results point out a need for the Institution to direct greater attention to feedback to teachers in the different links. An institutional policy is necessary to motivate and monitor their performance in the classroom